The new encyclopedia británica in 30 volumes, macropedia VOL.12 / William Benton - Benton, William (1977)
Formation and classification, of metamorphic rocks, physical and chemical characteristics, rocks of the principal facies, distribution of metamorphic rocks, origin of term, characterizations of metaphysics, metaphysics and other branches of philosophy, metaphysics and analysis, the existence of forms, categories, and particulars.